Food systems research to support sustainable impact - Béné, Christophe; Lundy, Mark; de Brauw, Alan; Brouwer, Inge D. (International Food Policy Research Institute, 2020)
Food systems, which are essential sources of food, but also of income and employment, especially for resource-poor populations in low- and middle-income countries (LMICs), are undergoing dramatic transformations. Driven by changes in diets, urbanization, longer supply chains, and new ways of purchasing and consuming foods, these transformations pose serious challenges to achieving healthy, environmentally sustainable, and inclusive food systems for all. Rates of undernutrition and micronutrient deficiencies are still stubbornly high, while overweight, obesity, and accompanying noncommunicable diseases are rising — with these multiple forms of malnutrition increasingly found within the same communities, households, or even individuals.